La lucha del pueblo maya por el territorio y los recursos bioculturales - Maya Lorena Pérez Ruiz (Les Cahiers ALHIM)
The difficulties related to political recognition of cultural diversity are well represented by the Mexican scenario. Under the pressure of social movements, this country leaved behind the politics of monocultural integration, in order to establish the recognition of Rights upon intercultural politics. The Mexican situation is intricated. In a side, the Rights of Indigenous population are recognized, but Mexican State put in application reforms up to the neoliberal model fostering the despoil of indigenous territories. The Maya people of Yucatan is an example of struggles of beekeepers against the transgenic soy plantations promoted by Mexican government and the transnational MONSANTO. Until now, the Maya beekeepers have managed to stop them.